In-line phase-contrast breast tomosynthesis: a phantom feasibility study at a synchrotron radiation facility. (3rd August 2016) - Bliznakova, K; Russo, P; Kamarianakis, Z; Mettivier, G; Requardt, H; Bravin, A; Buliev, I
Abstract: The major objective is to adopt, apply and test developed in-house algorithms for volumetric breast reconstructions from projection images, obtained in in-line phase-contrast mode. Four angular sets, each consisting of 17 projection images obtained from four physical phantoms, were acquired at beamline ID17, European Synchroton Radiation Facility, Grenoble, France. The tomosynthesis arc was  ±32°. The physical phantoms differed in complexity of texture and introduced features of interest. Three of the used phantoms were in-house developed, and made of epoxy resin, polymethyl-methacrylate and paraffin wax, while the fourth phantom was the CIRS BR3D. The projection images had a pixel size of 47 µ m  ×  47 µ m. Tomosynthesis images were reconstructed with standard shift-and-add (SAA) and filtered backprojection (FBP) algorithms. It was found that the edge enhancement observed in planar x-ray images is preserved in tomosynthesis images from both phantoms with homogeneous and highly heterogeneous backgrounds. In case of BR3D, it was found that features not visible in the planar case were well outlined in the tomosynthesis slices. In addition, the edge enhancement index calculated for features of interest was found to be much higher in tomosynthesis images reconstructed with FBP than in planar images and tomosynthesis images reconstructed with SAA. The comparison between images reconstructed by the two reconstruction algorithms shows an advantage for the FBP method in terms of better edge enhancement. Phase-contrast breast tomosynthesis realized in in-line mode benefits the detection of suspicious areas in mammography images by adding the edge enhancement effect to the reconstructed slices.